Moderate Ideology Of The Yellow Book (Kitab Kuning): (Study on the Moderation of the Kitab of Fatḥ al-Mu'īn Taught in Islamic Boarding Schools) - Iswahyudi; Safala, Udin; Izaar, Ahmad Shohibul (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
The Yellow Book (Kitab Kuning; an Islamic textbook taught in Islamic boarding schools) study on moderation is still at the surface stage. Various studies conducted by intellectuals such as Ni'am, Sahri, Kusmira, and Kholis have not fully shown how the moderation of the yellow book was produced. The explanation that the Yellow Book displays a variety of opinions from scholars on a matter is insufficient to justify the Yellow Book's moderation. This paper intends to perfect these shortcomings by displaying one yellow book that is an essential reference in Islamic boarding schools, Fatḥ al-Mu'īn. The Book of Fatḥ al-Mu’īn is a standard for mastering religious science in Islamic boarding schools. This book is taught to upper-class students, is complex to read, and powerfully connects with sanad transmission. The taking of legal justifications for disputed issues, even by large NU organizations, refers to the decision of this book Fatḥ al-Mu’īn. By using a critical, descriptive method, this paper seeks to find the acceptance of the Islamic boarding school towards the Book of Fatḥ al-Mu’īn and the model of the disclosure of the Book of Fatḥ al-Mu’īn, which is indicated as a form of moderation. This study found that the Book of Fatḥ al-Mu’īn was accepted by pesantren through transmitting the scientific knowledge of its founders, who were madhhab or al-Shafi'i ideology. Meanwhile, the model of moderation in the Book of Fatḥ al-Mu’īn is shown by mentioning other opinions after making conclusions, going out of the two extreme points, and choosing the priority of the views without blaming or judging. Abstrak Kajian kitab kuning tentang moderatisme saat ini masih pada tahap permukaan. Berbagai penelitian yang dilakukan oleh intelektual semacam Ni’am, Sahri, Kusmira dan Kholis belum menunjukkan secara lengkap bagaimana moderatisme kitab kuning tersebut diproduksi. Penjelasan bahwa kitab kuning menampilkan ragam pendapat dari para ulama tentang suatu masalah belum memadai untuk membuat justifikasi tentang moderatisme kitab kuning. Tulisan ini bermaksud menyempurnakan kekurangan tersebut dengan menampilkan satu kitab kuning yang menjadi rujukan penting di pesantren, yaitu Fatḥ al-Mu’īn. Kitab Fatḥ al-Mu’īn dijadikan standar penguasaan keilmuan agama di pesantren. Tidak saja, kitab ini diajarkan untuk santri kelas atas, tetapi juga karena kitab ini memiliki kerumitan tersendiri untuk dibaca dan memiliki ketersambungan transmisi sanad yang kukuh. Pengambilan justifikasi hukum untuk masalah-masalah yang diperselisihkan, oleh organisasi besar NU sekalipun, merujuk kepada keputusan kitab Fatḥ al-Mu’īn ini. Dengan menggunakan metode diskriptif kritis, tulisan ini hendak mencari penerimaan pesantren terhadap Kitab Fatḥ al-Mu’īn dan model pengungkapan Kitab Fatḥ al-Mu’īn yang diindikasi sebagai bentuk moderatisme. Penelitian ini menemukan bahwa Kitab Fatḥ al-Mu’īn diterima pesantren melalui transmisi keilmuan para pendirinya yang bermadzhab atau berideologi al-Shafi’i. Sedangkan model pengungkapan moderatisme Kitab Fatḥ al-Mu’īn ditunjukkan dengan menyebut pendapat lain setelah membuat kesimpulan, keluar dari dua titik ekstrim dan pemilihan prioritas pendapat tanpa menyalahkan atau menghakimi. Keywords: Fatḥ al-Mu’īn; Moderate; Islamic boarding schools; disclosure models